Freud's Jaw and Other Lost Objects : Fractured Subjectivity in the Face of Cancer - Lin, Lana (Book collections on Project MUSE., 2017)
Draws on psychoanalyst Melanie Klein's theories, among others, to examine the psychic effects of illness, in particular cancer, on the life and work of psychoanalyst Sigmund Freud, poet Audre Lorde, and literary theorist Eve Kosofsky Sedgwick. Also discusses psychic and material culture at the Freud Museums in London and Vienna.